2004
DOI: 10.1126/science.1098991
|View full text |Cite
|
Sign up to set email alerts
|

Frataxin Acts as an Iron Chaperone Protein to Modulate Mitochondrial Aconitase Activity

Abstract: Numerous degenerative disorders are associated with elevated levels of prooxidants and declines in mitochondrial aconitase activity. Deficiency in the mitochondrial iron-binding protein frataxin results in diminished activity of various mitochondrial iron-sulfur proteins including aconitase. We found that aconitase can undergo reversible citrate-dependent modulation in activity in response to pro-oxidants. Frataxin interacted with aconitase in a citrate-dependent fashion, reduced the level of oxidant-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
285
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 335 publications
(298 citation statements)
references
References 30 publications
10
285
3
Order By: Relevance
“…We have previously shown in vitro that when mitochondria are challenged with prooxidants, aconitase and the mitochondrial iron-binding protein frataxin interact. This interaction requires the enzyme's substrate citrate, protects the [4Fe-4S] 2ϩ cluster of aconitase from oxidant-induced disassembly, and is required for enzyme reactivation (24). Immunopurification of aconitase followed by Western blot analysis of frataxin revealed that the two proteins interacted exclusively during reperfusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown in vitro that when mitochondria are challenged with prooxidants, aconitase and the mitochondrial iron-binding protein frataxin interact. This interaction requires the enzyme's substrate citrate, protects the [4Fe-4S] 2ϩ cluster of aconitase from oxidant-induced disassembly, and is required for enzyme reactivation (24). Immunopurification of aconitase followed by Western blot analysis of frataxin revealed that the two proteins interacted exclusively during reperfusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Based on previous in vitro results (24), the interaction between aconitase and frataxin upon reoxygenation likely protects aconitase from prooxidant-induced cluster disassembly, irreversible inactivation, and degradation.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, 30% of the patients with NAFLD have elevated ferritin levels [139][140][141], and there is an association between insulin resistance and liver iron [142,143]. Therefore, it sounds rationale that iron causes oxidative stress because it is a well-known prooxidant and possesses negative effects upon the mitochondria [144,145]. However, ongoing additional studies at present indicate that iron is likely to be important in only a minority of patients with NAFLD.…”
Section: Ironmentioning
confidence: 99%
“…The decrease in frataxin protein has broad, far-reaching effects because the protein is an essential iron chaperone required for the biogenesis of iron-sulfur clusters, aconitase activation, and heme biosynthesis [18][19][20][21], and further performs a critical role in iron detoxification and anti-oxidant protection [22][23][24]. Thus a loss of frataxin leads to widespread impairment of energy metabolism, increased oxidative stress, and a generally dysregulated iron metabolism, including accumulation of iron in the heart and nervous system [25].…”
Section: Introductionmentioning
confidence: 99%